2008
DOI: 10.1007/s10800-008-9615-2
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and electrochemical performance of LiNiVO4 anode material for lithium-ion batteries

Abstract: A rheological phase reaction method was introduced to synthesize LiNiVO 4 powder material. The product was tested using XRD, SEM and electrochemical measurement methods. It was found that single crystal grain LiNiVO 4 is easily prepared with the rheological phase reaction; the intermediate product NiV(IV)O 3 is the electrochemical active center; the product prepared at 700°C for 18 h possess the best morphology of single crystal body and exhibits excellent performance as anode material with a small capacity fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
1
0
0
Order By: Relevance
“…Subsequently, the group of Tarascon 1098,1099 studied both crystalline and amorphous (hydrated) phases of LiNiVO 4 and found that they show capacity fading from ∼1000 mA•h g −1 to ∼550 mA•h g −1 after 50 cycles. Similar capacity fading in LiNiVO 4 was also reported by Han et al 1100 Shirakawa et al 1101,1102 studied in detail the Li−LiCoVO 4 system to understand the reaction mechanism. They found that at 0.02C and at 5C rates (1C = 350 mA g −1 ), reversible capacities of 980 and 800 mA•h g −1 are obtained.…”
Section: Ternary Oxidessupporting
confidence: 77%
“…Subsequently, the group of Tarascon 1098,1099 studied both crystalline and amorphous (hydrated) phases of LiNiVO 4 and found that they show capacity fading from ∼1000 mA•h g −1 to ∼550 mA•h g −1 after 50 cycles. Similar capacity fading in LiNiVO 4 was also reported by Han et al 1100 Shirakawa et al 1101,1102 studied in detail the Li−LiCoVO 4 system to understand the reaction mechanism. They found that at 0.02C and at 5C rates (1C = 350 mA g −1 ), reversible capacities of 980 and 800 mA•h g −1 are obtained.…”
Section: Ternary Oxidessupporting
confidence: 77%